Análise do desenvolvimento econômico na microrregião da Baixa Verde/RN - Vital, Luis Victor Matias (Universidade Federal Rural do Semi-Árido, 2020)
The economic development of a given state or region has always been a subject of great relevance, as it measures, analyzes, studies and guides the development capacity of a given state. This brought the economic development of the microregion of mato grande, which is located in the territory of Rio Grande do Norte, which is composed of five cities, namely João Câmara/RN, Jandaíra/RN, Parazinho/RN, Poço Branco/RN and Bento Fernandes/RN. Analyzes of the emergence of cities were made with their respective breakdowns, demographic analyzes were made and the comparison of the GDP per capita of each city studied bringing the comparison on a national, state and micro-region scale. With that, it was showing the development of each city happened and showing the specific reasons for its recent and older development. Other factors that were taken into account, was how each city developed according to the divisions of its enterprises. Another question that was taken based on was the demonstration of the descriptive study taken based on the methodology, where it sought to guide the research model adopted. Regarding the results obtained in the research, it can be said that they were of excellent quality, based on sources of study on exactly each city studied. And with that it was demonstrated how the studied city developed and also showing the prominence of João Câmara / RN.
Artigo
Keywords: Desenvolvimento; Microrregião; Economia; Development; Microregion; Economy; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA